Factors Influencing Prescribing of Statins in Singapore Compared to Queensland, Australia - Curran, R.; Bernaitis, N.; Davey, A.; Hattingh, H. Laetitia; McFarlan, A.; Ching, E.; Chong, T.; Ching Chi Keong, C.; Anoopkumar-Dukie, S. (2016)
HMG-CoA reductase inhibitors (statins) are widely prescribed for dyslipidaemia with established benefits in reducing cardiovascular disease mortality and morbidity. Controversy remains surrounding statin use in low risk patients and patients of certain ethnicities. The aim of this study was to identify factors which influence the prescribing of statins by interviewing doctors from Queensland, Australia and Singapore. Purposive interviews were conducted with prescribers in Queensland Australia (n=20) and Singapore (n=21) to determine factors influencing statin prescribing. Cost, availability of generics and statin potency were major factors significantly influencing Singaporean prescribers compared to Australian prescribers (p<0.05). Although not significant, the potential for drug interactions also impacted statin prescribing in Singapore compared to Australia (p=0.0516). Cost and statin potency were major factors influencing the prescribing of statins in Singapore compared to Australia. Patients may be prescribed the cheaper, less potent statins potentially resulting in reduced patient benefits.